1,4-Di-n-octyl-1,2,3,4-tetrahydroquinoxaline-2,3-dione - Khadija El Bourakadi; Youness El Bakri; Jihad Sebhaoui; Ibtissam Rayni; El Mokhtar Essassi; Joel T. Mague (IUCrData, 2017)
In the title compound, C24H38N2O2, the heterocyclic ring (r.m.s. = 0.015 Å) deviates from planarity to a greater extent than the benzene ring (r.m.s. deviation = 0.007 Å). In the crystal, the molecules pack to form polar and non-polar regions. The major intermolecular interaction appears to be complementary π-stacking between oppositely oriented tetrahydroquinoxaline units.